Nimrod Workman. - Workman, Nimrod; Congo, Paul.; Wright, Jackie; Broadside Press (Johnson City, Tenn. : Broadside Press, 1977)
79 year old Nimrod Workman's music is very much reflective of his experiences, and in this tape he moves from anecdotes to songs and back again without any sense of self-consciousness or artificiality. Topics covered include coal-mining, the union struggle, black lung, herb gathering and the Hatfield-McCoy feud.
U standard.
Keywords: Folk songs, English -- Appalachian Region, Southern; Ballads, English -- Southern States